Pengaruh Tagline Promosi “It’s Glowtime” Produk Iphone 16 Terhadap Minat Beli Konsumen : Studi Regresi Pada Mahasiswa Fakultas Ekonomi Universitas Muhammadiyah Sukabumi - Jindan, Yasmin Vairus (Brand Communication, 2025)
The purpose of this study is to examine the influence of the tagline “It’s Glowtime” for the iPhone 16 on consumer purchase intention among economics students at Universitas Muhammadiyah Sukabumi, and to analyze how significant that influence is. This research is driven by Apple’s 24% increase in sales in Q1 2024 compared to Q1 2020. The study aims to determine whether an attractive tagline has a significant impact on consumer buying interest. A quantitative method was used, involving 100 active students from the Faculty of Economics at Universitas Muhammadiyah Sukabumi as respondents. An online questionnaire was distributed to gather information on familiarity, differentiation, message of value, transactional interest, referential interest, preferential interest, and exploratory interest. The results show that the independent variable, namely the tagline “It’s Glowtime,” affects consumer purchase intention toward the iPhone 16. This research concludes that the tagline successfully contributes to generating interest and shaping a strong purchase intention among the target audience. Further research is recommended to explore a broader range of factors that may influence consumer buying interest in more depth.